The influence of service quality and brand image on customer satisfaction at CCTV Palace Medan - Hendry, Hendry; Hengky Kosasih (Paspama Institute, 2024)
The study was conducted to test and analyze the influence on service quality and brand image on customer satisfaction at Istana CCTV Medan. The research used a quantitative research approach, while this type of research is a quantitative associative study. The research population were 355 customers and the research samples consisted of 78 customers, drawn by using simple random sampling techniques. The research data were analyzed using multiple linear regression methods and classical assumption testing. Partially, the results on study showed that service quality and brand image had a positive and significant effect on customer satisfaction at Istana CCTV Medan. Simultaneously, service quality and brand image have a positive and significant effect on customer satisfaction at Istana CCTV Medan. The value on adjusted R2 was 0,626, meaning that the variable variation in customer satisfactioncan be explained by the two independent variables up to62.6% and the remaining 37.4% can be explained by other variables